Exercise training induces insulin-sensitizing PAHSAs in adipose tissue of elderly women - Brezinova, Marie; Cajka, Tomas; Oseeva, Marina; Stepan, Marek; Dadova, Klara; Rossmeislova, Lenka; Matous, Milos; Siklova, Michaela; Rossmeisl, Martin; Kuda, Ondrej (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2020)
Adverse effects of aging can be delayed with life-style interventions. We examined how exercise training (ET) alone or combined with omega-3 polyunsaturated fatty acid (PUFA) affects serum and adipose tissue (AT) lipidome in older women. Fifty-five sedentary older women were included in the physical activity program and given either sunflower (Placebo) or wax esters-rich (Calanus) oil capsules for 4 months. Serum and subcutaneous abdominal AT samples were acquired while maximum rates of oxygen consumption (VO2 max), insulin sensitivity (hyperinsulinemic-euglycemic clamps) and comprehensive lipidome profiles were determined before and after the study. ET increased VO2 max in both groups. Lipidomics profiling revealed unusual serum triacylglycerols and phospholipids with ether-bound alkyls in the Calanus group, while ET generally induced shorter-chain triacylglycerols in AT, suggesting increased de novo lipogenesis. The latter was positively associated with whole-body insulin sensitivity. Unexpectedly, insulin-sensitizing lipokines from the family of branched palmitic acid esters of hydroxy stearic acid (PAHSAs) were elevated in both serum and AT after ET, while PAHSAs-containing triacylglycerols were detected in AT. ET stimulated beneficial changes in AT, including PAHSAs synthesis. Although the added value of omega-3 PUFA supplementation was not proven, our discovery can help understand the nature of the metabolic benefits of exercise.
Keywords: Female; Dietary Supplements; Esters; FAHFA-TG; Exercise; Metabolic Syndrome; inzulin; FAHFA; Lipidomics; estery; tuková tkáň; senioři nad 80 let; omega-3 mastné kyseliny; Humans; Omega-3 fatty acids; Lipogenesis; Fatty Acids, Omega-3; Mass spectrometry; stárnutí; cvičení; potravní doplňky; kombinovaná terapie; lidé; Ether lipids; lipidomika; Aging; Adipose Tissue; Lipokine; lipogeneze; Aged, 80 and over; senioři; Palmitic Acid; kyselina palmitová; Treatment Outcome; ženské pohlaví; Combined Modality Therapy; Adipose tissue; PAHSA; Aged; Elderly women; metabolický syndrom; Insulin; Stearic Acids; výsledek terapie; kyseliny stearové